PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) PADA PEMBELAJARAN MENULIS TEKS NEGOSIASI DI KELAS X SMK LENTERA BANGSA - Siti Patonah; Ahmad Syahrullah; Dida Firmansyah; Diena San Fauziya (IKIP Siliwangi, 2018)
In relation to the enactment of the Curriculum 2013 on the final activity in learning the students are required to be able to make the text, then the students must be trained to write in order to be skilled, especially writing the negotiation text. However, sometimes students are still not fully familiar with the text that will be studied, students are still confused about forming structure, rules, character, and linguistic. Students can not just to know or know the form of text only but must practice it by writing directly. Writing the negotiating text on class X TKJ 1 runs effectively and the grade increase has been successful. This research uses experimental method (one group pretest-posttest design). The results of this study there is an average value of the initial test 47.5 and the final test 71.5 so there is a difference in this study and based on statistical calculations obtained t = 4.84> t table = 2.09 which means that the final test results better than the initial test as well as the PBL model is very effectively used in learning writing negotiating text.